Philippine modernities and their contradictions cultural responses, contentions, imaginaries - Van Der Wall, Hidde (2020)
Impressive in its scope, Philippine modernities: music, performing arts and language 1880-1941, edited by University of the Philippines musicologist Jose S. Buenconsejo, reminds of the various, multiple and complex ways that Philippine culture and arts were entangled in processes of modernity. A good number of the essays collected in the volume offer insights into the complexities, conflicts and ambiguities that ensued as colonial Philippine culture and society underwent developments related to modernity. But the volume does not entirely fulfill this potential as many of the essays resort to dichotomous views of local and foreign, homogenizing notions o nation, and a one-way concept of the relationship between economic and cultural developments. Modernism, as a set of styles that express and constitute modern mentalities, receives little attention, as do analyses from alternative perspective like class, gender, and ethnicity Nevertheless, the book is an important contribution to the growing body of research on Philippine (post) colonial culture.
Keywords: Philippine culture; Arts, Philippine; Modernism (Art)